Documents from Halle - Haustierkundliche Sammlung (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2019)
RDF file containing bibliographical references from archive in Halle.
Keywords: Archival materials; Animal breeding; Karakul sheep; Agriculture; Germany; Halle; Karakul Farming; Karakul Sheep Industry